1997
DOI: 10.1177/0146167297231004
|View full text |Cite
|
Sign up to set email alerts
|

Are Americans more Optimistic than the Chinese?

Abstract: A total of 613 subjects, including257 White American students, 312 mainland Chinese students, and 44 Chinese American students, completed the Attributional Style Questionnaire. It was found that (a) mainland Chinese were more pessimistic than Chinese Americans, who were more pessimistic than White Americans, (b) mainland Chinese were less self-blaming (i.e., attributed their failure less internally than the traditional Chinese culture expects) and attributed their success to other people or circumstances, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 33 publications
14
104
0
5
Order By: Relevance
“…Respondents who are more likely to endorse both positive and negative outcomes would give the impression that they have neutral views when, in fact, they see both negative and positive aspects of the environment. Nevertheless, several studies that have measured optimism and pessimism using bidimensional scales have shown support for the unidimensional nature of optimism and pessimism (Chang, Maydeu-Olivares, & D'Zurilla, 1997;Lee & Seligman, 1997). Therefore, results from the unidimensional EFS employed in the present study may well be a good approximation of those that might be obtained from a similar bidimensional scale.…”
Section: Limitationssupporting
confidence: 50%
“…Respondents who are more likely to endorse both positive and negative outcomes would give the impression that they have neutral views when, in fact, they see both negative and positive aspects of the environment. Nevertheless, several studies that have measured optimism and pessimism using bidimensional scales have shown support for the unidimensional nature of optimism and pessimism (Chang, Maydeu-Olivares, & D'Zurilla, 1997;Lee & Seligman, 1997). Therefore, results from the unidimensional EFS employed in the present study may well be a good approximation of those that might be obtained from a similar bidimensional scale.…”
Section: Limitationssupporting
confidence: 50%
“…Indeed, crosscultural studies suggest that East Asians report lower self-esteem and hedonic well-being than European Americans (Boucher, Peng, Shi, & Wang, 2009;Hamamura, Heine, & Paulhus, 2008;Heine & Lehman, 1997;Lee & Seligman, 1997;Spencer-Rodgers et al, 2004;Steger, Kawabata, Shimai, & Otake, 2008). Given the expected relationship between SDT need satisfaction and well-being, we anticipated that perceived satisfaction of SDT needs would also be lower in dialectical cultures.…”
Section: Cultural Dimensions Sdt Needs and Well-beingmentioning
confidence: 96%
“…Our predictions regarding cultural differences in need satisfaction were largely inferred from the more extensive literature on cultural differences in well-being, in which lower dialecticism (or non-East Asian cultural membership) and greater individualism have been associated with greater self-esteem and hedonic well-being (Boucher et al, 2009;Hamamura et al, 2008;Heine et al, 1999;Heine & Lehman, 1997;Lee & Seligman, 1997;Sheldon et al, 2011;Spencer-Rodgers et al, 2004). Our finding that participants in the Asian cultures averaged lower on most of the measures of eudaimonic well-being and the well-being component was consistent with these studies and our mediation analyses again supported an interpretation in terms of dialecticism and independent selfconstruals.…”
Section: Cultural Differences In Need Satisfaction and Well-beingmentioning
confidence: 99%
“…De fato, ilusões positivas como auto-engrandecimento, otimismo ingênuo e percepções exageradas de controle são comuns entre norte-americanos e funcionam como mecanismos de coping para restaurar e manter saúde física e psicológica positiva dos americanos (Taylor & Armor, 1996). Contudo, recentes estudos transculturais (Lee & Seligman, 1997) descobriram que tais ilusões positivas não são comuns entre asiáticos, sugerindo que auto-engrandecimento e otimismo podem não conduzir a elevado BES em determinadas culturas.…”
Section: A S Albuquerque E B T Tróccoliunclassified